2012
DOI: 10.7314/apjcp.2012.13.2.527
|View full text |Cite
|
Sign up to set email alerts
|

An integrated Approach to Worksite Tobacco Use Prevention and Oral Cancer Screening Among Factory Workers in Mumbai, india

Abstract: Background: Tobacco control and cessation interventions are among the most cost effective medical interventions but health systems in low resource countries lack the infrastructure to promote prevention and cessation among tobacco users. Workplace settings have the potential to provide opportunities and access for tobacco prevention interventions. Methods: This is a single group study evaluating tobacco use prevention and cessation through a structured three stage intervention program for tobacco users compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…A large (~100,000 individuals) cross-sectional survey conducted in the city of Mumbai [16] also reported that the prevalence of tobacco use varied across occupational categories, with the highest tobacco use observed among unskilled workers (76%) and the lowest among professionals (45%). Studies in other Indian manufacturing worksites also reported high (ranges from 39% to 86%) prevalence of tobacco use among production workers [17][18][19][20][21]. Taken together, these findings indicate that tobacco use prevalence among production workers varies across India and is mostly higher than the prevalence among nonproduction workers or the general population [2].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…A large (~100,000 individuals) cross-sectional survey conducted in the city of Mumbai [16] also reported that the prevalence of tobacco use varied across occupational categories, with the highest tobacco use observed among unskilled workers (76%) and the lowest among professionals (45%). Studies in other Indian manufacturing worksites also reported high (ranges from 39% to 86%) prevalence of tobacco use among production workers [17][18][19][20][21]. Taken together, these findings indicate that tobacco use prevalence among production workers varies across India and is mostly higher than the prevalence among nonproduction workers or the general population [2].…”
Section: Discussionmentioning
confidence: 87%
“…Studies in India from worksites [18][19][20][21] and from the general population [16,17,[29][30][31][32] have reported an inverse association between SES (in terms of education and economic index) and tobacco use, with the highest tobacco use among those with lowest SES. In this study, in addition to an increase in current tobacco-use with decreasing education, past tobacco use decreased with decreasing education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Worksite intervention techniques have proved to be more effective than the clinic based intervention techniques (Fiore and Baker, 2011;Hughes et al, 2011;Pimple et al, 2012a;2012b). However this study was unique as the counseling was done by a dentist at the worksite.…”
Section: Resultsmentioning
confidence: 99%